Prevalence of asthma and wheeze in the Highlands of Scotland. - Austin, J B (1994)
To establish the prevalence of asthma and wheeze in 12 year old children in a region with low background pollution levels, a population of children resident in the Highland Region of Scotland was studied by questionnaire supported by objective data. A respiratory questionnaire was distributed to the parents of 1919 children aged from 12-13 years and attending secondary schools in the educational divisions of Lochaber, Ross and Cromarty, and Inverness including Skye in Highland Region to ascertain history of wheeze and parental awareness of a diagnosis of asthma. Peak expiratory flow (PEF) measurements were carried out before and after a standardised exercise test. Ozone levels were noted. Questionnaires were completed by 1825 parents (95% of those invited) and 1702 (93%) of those returning questionnaires took part in the exercise test. The overall prevalence of reported asthma was 14% and wheeze 25%. Defined as a fall in PEF of more than 15% with exercise, the overall prevalence of exercise induced bronchospasm was 9%. In Skye the prevalence of reported asthma was 17%, wheeze 28%, and exercise induced bronchospasm 30%. There were no significant differences between areas for reported asthma or wheeze. There was, however, a highly significant difference between areas for exercise induced bronchospasm, most of which was accounted for by the very high incidence in Skye, which is one of the most rural of the areas studied. The results of this study do not support the hypothesis that asthma is commoner in urban than rural areas, whether we compare the Highlands with the rest of the UK or areas within the Highlands, or whether we examine reported symptoms or exercise induced bronchospasm. The results do not support an association between atmospheric pollution and the prevalence of asthma.